Social Listening Analysis of information patterns and public perception of Lassa fever, Diphtheria, and Cerebrospinal Meningitis in Nigeria - Dr Kemisola Agbaoye; Miss Sonia Biose; Mr Sunday Oko; Mr Abara Erim; Miss Favour Ani; Mrs Vivianne Ihekweazu; Miss Anwuli Nwankwo (International Journal of Infectious Diseases)
Introduction: Infectious diseases continue to be a burden globally as they ignore geographic and political boundaries. The potential for illnesses, disability, and death from biological threats—both naturally occurring and purposefully introduced—is growing. Nigeria is concurrently responding to three major infectious disease outbreaks: Lassa fever, diphtheria, and meningitis. This study used an AI-powered social listening tool to determine information patterns and public perception about Lassa fever, Diphtheria, and Cerebrospinal Meningitis in Nigeria. Methodology: Social listening data on Lassa fever, Diphtheria and Meningitis was retrospectively mined between December 2023 and March 2024 using Determ media monitoring software. A range of digital locations, including news articles, blogs, and social media platforms (Twitter, Facebook, Instagram, and YouTube), were monitored for discussions pertaining to the diseases. To gather all references and analyse them topically, predefined prioritising indicators were employed. These indicators included analysis based on discussion volume, reach, and engagement. Results: The largest number of conversations on Lassa fever occurred on Twitter (2,194) and News media/blogs for Diphtheria (1,064) and Meningitis (291), respectively. The total reach of Lassa fever-related content across all platforms increased significantly over time, with 183% for Meningitis-related conversations on Twitter and 23.8% for Diphtheria on news media and blogs. Overall interactions of Lassa-fever increased by over 100% across all the platforms; news media/blogs accounted for 94% for meningitis and a significant increase on Twitter for diphtheria. Overall, there was a significantly progressive increase in the conversation volume on the three infectious diseases, indicating public eagerness for accessible and accurate information about preventive measures, symptoms, and available treatments. Some levels of health misinformation related to the selected infectious diseases were also identified. Discussion: This study shows how important these platforms are as a source of disseminating health information and engaging in conversations regarding infectious diseases. Based on current evidence and data from other studies, communicating accurate health information significantly improves adherence to preventive behaviour in public health response management, and behaviour change is the goal of accurate health communication. Online platforms are increasingly becoming more viable for public health information dissemination during infectious disease outbreaks. Conclusion: The levels of engagement and reach highly demonstrate the public's strong interest in acquiring information from various web sources. Therefore, to guarantee the appropriate dissemination of accurate information and campaigns across the various online channels, strategic and sustainable awareness is recommended to educate the public about the diseases' symptoms, transmission, and preventive measures. Also, capacity building is recommended for public health agencies and healthcare workers to increase engagement on Twitter to address concerns, answer questions, and dispel myths about the disease outbreak.